DAMPAK RELATIONSHIP MARKETING DAN STORE ATMOSPHERE MELALUI KEPUASAAN PELANGGAN TERHADAP LOYALITAS - Ilma Liana; Sitindaon, Nikson; Damanik, Sri Winda Hardiyanti (Economic Development Progress, 2022)
The research objective is to see and analyze the impact of relationship marketing and store atmosphere on customer loyalty by using satisfaction as an intervention variable. This type of research is quantitative. The sample in this study were 92 respondents and the sampling technique used was purpositive. Data collection was carried out by distributing questionnaires to respondents who visited more than once using a Likert scale. Using the SPSS 25.00 tool, the t-test and path analysis yielded the following results. Relationship marketing and Store Atmosphare have an influence on customer loyalty variables. where tcount > ttable. Relationship marketing and store atmosphere affect the satisfaction variable, tcount > ttable. Customer satisfaction has no effect on customer loyalty variables. Meanwhile, customer satisfaction cannot mediate relationship marketing and store atmosphere on customer loyalty.